2020
DOI: 10.15376/biores.15.4.7357-7373
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nanocellulose on alginate/gelatin bio-inks for extrusion-based 3D printing

Abstract: Cellulose nanofibers (NFC) have attracted special attention in the field of extrusion-based three-dimensional (3D) bioprinting due to their good biocompatibility, excellent mechanical properties, and outstanding shear-thinning property. In this study, by mixing cellulose nanofibers suspension with sodium alginate (SA) and gelatin (GEL) solution, five groups of composite bio-inks with different NFC concentrations were prepared. The effects of NFC on the performance of the SA/GEL matrix hydrogels were analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 48 publications
5
13
0
Order By: Relevance
“…This consistency suggests that the gelled formulations are able to retain their shapes with good shape fidelity post extrusion [37,38 It is important to note that bioinks with good shape fidelity will contribute to hig accuracy and resolution of a printed scaffold. This finding also corroborated that th addition of CNC has a positive effect on the shape fidelity of the gelled formulations probably due to the increased interactions between the hydrogel networks [16,18].…”
Section: Determination Of Storage and Loss Moduli Of Cnc/alg/pegda Gelled Formulationssupporting
confidence: 74%
See 3 more Smart Citations
“…This consistency suggests that the gelled formulations are able to retain their shapes with good shape fidelity post extrusion [37,38 It is important to note that bioinks with good shape fidelity will contribute to hig accuracy and resolution of a printed scaffold. This finding also corroborated that th addition of CNC has a positive effect on the shape fidelity of the gelled formulations probably due to the increased interactions between the hydrogel networks [16,18].…”
Section: Determination Of Storage and Loss Moduli Of Cnc/alg/pegda Gelled Formulationssupporting
confidence: 74%
“…It is important to note that bioinks with good shape fidelity will contribute to high accuracy and resolution of a printed scaffold. This finding also corroborated that the addition of CNC has a positive effect on the shape fidelity of the gelled formulations, probably due to the increased interactions between the hydrogel networks [16,18]. Upon manual extrusion and double crosslinking treatment using ionic (Ca 2+ ) and UV irradiation at 365 nm, the physical characteristics of the CNC/Alg/PEGDA formulations were observed.…”
Section: Determination Of Storage and Loss Moduli Of Cnc/alg/pegda Gelled Formulationssupporting
confidence: 69%
See 2 more Smart Citations
“…Nanocellulose is derived principally from bacteria [163], and its use, combined with other bioinks, integrates the common properties of the cellulose: high stiffness, modulus, hydrophilicity, and thermal stability. For example, Han et al studied the effect of nanocellulose on alginate/gelatin bioinks [164]. Their result showed that the incorporation of a small amount of nanocellulose improved the printability, stability, and fidelity of the structure, but high amounts of nanocellulose promoted a negative impact on the elongation and compression yield.…”
Section: Evolution Of the Bioinksmentioning
confidence: 99%